Power generation unit

JP7637941B2Active Publication Date: 2025-03-03TOKYO OHKA KOGYO CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021028897
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-25
Publication Date
2025-03-03
Estimated Expiration
2041-02-25

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、多孔質構造を有する帯電フィルムを用いることによって帯電フィルムが帯びる電気量を増加させることが可能となるので、大型化を抑制するととともに発電量を増加させることが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637941000002
    Figure 0007637941000002
  • Figure 0007637941000003
    Figure 0007637941000003
  • Figure 0007637941000004
    Figure 0007637941000004
Patent Text Reader

Abstract

To provide a power generation body capable of suppressing an increase in size and increasing a power generation amount.SOLUTION: A power generation body 1 comprises a first member 10 having a first surface 11a covered with a first charging film 12 and a second member 20 having a second surface 21a covered with a second charging film 22. The power generation body generates power by changing the state of mutual contact between the first surface 11a and the second surface 21a. The first surface 11a and the second surface 21a are provided with uneven structures 11a1 and 21a1 formed over the entire surface, and the second charging film 22 consists of a member with porous structure.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a power generating unit that generates electricity by utilizing frictional electrification. [Background technology]

[0002] A known conventional generator comprises a first member having a first surface covered with a first charged film and a second member having a second surface covered with a second charged film, and generates electricity by changes in the contact state between the first surface and the second surface (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-191454 A Summary of the Invention [Problem to be solved by the invention]

[0004] When the power generating unit is to be increased in power generation capacity in order to supply power to an electrical device consuming large amounts of power, it is possible to increase the contact area between the first surface of the first member and the second surface of the second member. In this case, the power generating unit becomes larger, which may limit the places where the power generating unit can be installed, resulting in a decrease in versatility.

[0005] An object of the present invention is to provide a power generator which is capable of suppressing an increase in size and increasing the amount of power generated. [Means for solving the problem]

[0006] The generator of the present invention comprises a first member having a first surface covered with a first charged film and a second member having a second surface covered with a second charged film, and generates electricity by changing the contact state between the first surface and the second surface, wherein at least one of the first surface and the second surface has an uneven structure formed over the entire surface, and at least one of the first charged film and the second charged film is formed from a material having a porous structure.

[0007] Furthermore, in the power generating body of the present invention, preferably, when the uneven structure is formed on only one of the first surface and the second surface, the height from the bottom to the top of the uneven structure is 0.3 mm or more, and when the uneven structure is formed on both the first surface and the second surface, the sum of the height from the bottom to the top of the uneven structure formed on the first surface and the height from the bottom to the top of the uneven structure formed on the second surface is 0.3 mm or more.

[0008] In the power generating unit according to the present invention, preferably, one of the first charged film and the second charged film is made of polyimide having a porous structure, and the other is made of polyamide.

[0009] In the power generating unit according to the present invention, the member having the porous structure preferably has pores with an average diameter of 200 nm or more and 400 nm or less. Effect of the Invention

[0010] According to the present invention, by using a charged film having a porous structure, it is possible to increase the amount of electricity carried by the charged film, thereby making it possible to prevent the film from becoming large and to increase the amount of power generation. [Brief description of the drawings]

[0011] [Figure 1] 1 is a cross-sectional view of a power generating unit according to an embodiment of the present invention. [Diagram 2]1 is a cross-sectional view of a power generating unit showing a state in which a force is applied from the outside to a first member and a second member in one embodiment of the present invention. [Diagram 3] FIG. 2 is a cross-sectional view of a main portion of a second charging film according to one embodiment of the present invention. [Figure 4] 11 is a graph showing test results regarding the generated voltage of a comparative example of a power generator that does not have a concave-convex structure according to one embodiment of the present invention. [Diagram 5] 1 is a graph showing test results regarding the generated voltage of power generators of an example and a comparative example having a concave-convex structure according to one embodiment of the present invention. [Figure 6] 4 is a graph showing the relationship between the number of times of power generation and the amount of power generation according to one embodiment of the present invention. [Figure 7] 1 is a graph showing the relationship between the sum of the heights of the concave-convex structures and the output fluctuation rate according to an embodiment of the present invention. [Figure 8] 6 is a graph showing the relationship between the pore size of a second charging film and the generated voltage according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Fig. 1 to Fig. 8 show an embodiment of the present invention. Fig. 1 is a cross-sectional view of a generator, Fig. 2 is a cross-sectional view of a generator showing a state in which a force is applied from the outside, Fig. 3 is a cross-sectional view of a main part of a second charged film, Fig. 4 is a graph showing the results of a test on the generated voltage of a comparative generator having no concave-convex structure, Fig. 5 is a graph showing the results of a test on the generated voltage of a generator of an embodiment and a comparative example having a concave-convex structure, Fig. 6 is a graph showing the relationship between the number of times of power generation and the amount of power generation, Fig. 7 is a graph showing the relationship between the sum of the heights of the concave-convex structure and the output fluctuation rate, and Fig. 8 is a graph showing the relationship between the pore diameter of the second charged film and the generated voltage.

[0013] The power generating unit 1 of this embodiment is provided, for example, on a tire of a vehicle, and generates power by receiving a force acting on the tire when the vehicle is traveling.

[0014] The power generating body 1 generates electricity by utilizing frictional electrification, and includes a first member 10 and a second member 20 that are oppositely charged depending on changes in their contact state, and a holding member 30 for holding the first member 10 and the second member 20 together.

[0015] The first member 10 has a first electrode portion 11 and a first charged film 12 that covers a first surface 11a of the first electrode portion 11 that is located on the second member 20 side.

[0016] The first electrode section 11 is made of a material having both electrical conductivity and elasticity. The first electrode section 11 is formed by covering the surface of an electrically conductive elastomer or an insulating elastomer such as nitrile rubber or silicone rubber with a conductive film of silver, copper, or the like. The conductive film is formed of, for example, a conductive nonwoven fabric.

[0017] An uneven structure 11a1 having a continuous wave shape is formed over the entire surface of the first surface 11a of the first electrode portion 11. The uneven structure 11a1 is formed to have a predetermined height H1 from the bottom to the top.

[0018] The first charged film 12 is made of a soft material that is insulating and charged with a polarity opposite to that of the second charged film described below. The first charged film 12 is selected from the group consisting of, for example, polymethyl methacrylate, nylon, polyvinyl alcohol, polyester, polyisobutylene, polyurethane, polyethylene terephthalate, polyvinyl butyral, polychloroprene, natural rubber, polyacrylonitrile, polydiphenol carbonate, polystyrene, polyethylene, polypropylene, etc. The first charged film 12 is formed to a thickness dimension T1 and covers the first surface 11a so as to follow the uneven structure 11a1.

[0019] The second member 20 has a second electrode portion 21 and a second charged film 22 that covers a second surface 21a of the second electrode portion 21 that is located on the first member 10 side.

[0020] The second electrode section 21 is made of a material having both electrical conductivity and elasticity. The second electrode section 21 is formed by covering the surface of an electrically conductive elastomer or an insulating elastomer such as nitrile rubber or silicone rubber with a conductive film of silver, copper, or the like. The conductive film is formed of, for example, a conductive nonwoven fabric.

[0021] An uneven structure 21a1 having a continuous wave shape is formed over the entire surface on the second surface 21a of the second electrode portion 21. The uneven structure 21a1 is formed to have a predetermined height H2 from the bottom to the top.

[0022] The second charged film 22 is made of a soft material that is insulating and is charged with the polarity opposite to that of the first charged film 12. The second charged film 22 is made of, for example, polyimide. The second charged film 22 is formed to a thickness dimension T2 and covers the second surface 21a so as to conform to the uneven structure 21a1. As shown in FIG. 3, the second charged film 22 has a porous structure having a large number of pores 22a and communicating holes 22b that communicate with adjacent pores 22a. The average pore diameter D of the pores 22a of the second charged film 22 is preferably within a range of 200 nm to 400 nm, and the average pore diameter d of the communicating holes 22b is preferably one-third or less of the average pore diameter D. The second charged film 22 preferably has a porosity of 50% or more, and desirably has holes on its surface from the viewpoint of increasing the specific surface area for the purpose of improving charging properties. The upper limit of the porosity is not particularly limited, but is, for example, 85% or less, and is preferably 80% or less in terms of film strength and the like.

[0023] The second charged film 22 can be produced, for example, by removing the fine particles from a composite film containing a resin as a base material or a precursor resin of the resin as a base material and fine particles to form the pores 22a. Examples of the resin as a base material or its precursor resin include polyimide resins or precursor resins of polyimide resins. The porous film constituting the second charged film 22 can be produced by a known method, for example, by the production method described in Japanese Patent No. 5745195 or Japanese Patent No. 6147069. When the second charged film 22 is a polyimide porous film, a part of the imide bond of the polyimide may contain an amide bond in which the ring is opened, but in terms of the processability of the power generating body according to the present invention, it is preferable that the polyimide does not contain an amide bond, and this can be confirmed by an FT-IR device.

[0024] Here, the sum of the height H1 of the uneven structure 11a1 of the first surface 11a and the height H2 of the uneven structure 21a1 of the second surface 21a is preferably 0.3 mm or more, more preferably 0.6 mm or more. The sum of the height H1 of the uneven structure 11a1 and the height H2 of the uneven structure 21a1 includes a case where the uneven structure is formed only on one of the first surface 11a and the second surface 21a, and the other is formed in a flat shape. For example, when the first surface 11a has the uneven structure 11a1 and the second surface 21a is flat, the height H1 of the uneven structure 11a1 is preferably 0.3 mm or more, more preferably 0.6 mm or more. Also, when the first surface 11a is flat and the second surface 21a has the uneven structure 21a1, the height H2 of the uneven structure 21a1 is preferably 0.3 mm or more, more preferably 0.6 mm or more.

[0025] It is preferable that the thickness dimension T1 of the first charged film 12 or the thickness dimension T2 of the second charged film 22 be 80 μm or less. Furthermore, it is more preferable that the thickness dimension T1 of the first charged film 12 and the thickness dimension T2 of the second charged film 22 are each 80 μm or less.

[0026] In addition, the first electrode portion 11 and the second electrode portion 21 are electrically connected to each other via an external load to which the generated power is supplied, and when a potential difference occurs between the first electrode portion 11 and the second electrode portion 21, electrons flow between the first electrode portion 11 and the second electrode portion 21.

[0027] As shown in FIG. 1, the holding member 30 is a member that holds the first member 10 and the second member 20 together in a state in which the first surface 11a of the first member 10 and the second surface 21a of the second member 20 face each other.

[0028] The power generating body 1 configured as described above generates electricity by switching between a first state in which no force is acting from the outside on the first member 10 and the second member 20 in a direction pressing the first charged film 12 and the second charged film 22 against each other, and a second state in which a force is acting from the outside in a direction pressing the first charged film 12 and the second charged film 22 against each other.

[0029] In the first state, the first charged film 12 and the second charged film 22 are in contact with each other, but since the first charged film 12 formed along the uneven structure 11a1 and the second charged film 22 formed along the uneven structure 21a1 face each other, the contact area between the first charged film 12 and the second charged film 22 is small.

[0030] On the other hand, in the second state, by applying a force in a direction pressing the first charged film 12 and the second charged film 22 against each other, the elastic concave-convex structure 11a1 of the first electrode portion 11 and the concave-convex structure 21a1 of the second electrode portion 21 are each deformed, and the contact area between the first charged film 12 and the second charged film 22 becomes larger than the contact area in the first state, as shown in Fig. 2. At this time, the first charged film 12 and the second charged film 22 rub against each other, so that the first member 10 is positively charged and the second member 20 is negatively charged.

[0031] Furthermore, when the force acting in the direction pressing the first surface 11a and the second surface 21a against each other is released from the second state, the first state is restored by the elastic forces of the first electrode portion 11 and the second electrode portion 21. At this time, electricity flows between the first electrode portion 11 and the second electrode portion 21 in a direction that makes the electric potentials equal. EXAMPLES

[0032] The present invention will now be described in detail with reference to examples.

[0033] As shown in Table 1, power generators of Comparative Example 1-7 and Example 1-5 were constructed by changing the material of the first charged film 12 of the first member 10 and the height H1 of the uneven structure 11a1, and the material of the second charged film 22 of the second member 20 and the height H2 of the uneven structure 21a1, respectively, and tests were conducted to evaluate the performance of each power generator.

[0034] [Table 1]

[0035] <Comparative Example 1> In comparative example 1, the first surface 11a of the first member 10 does not have an uneven structure 11a1, the first charged film 12 is polyurethane without a porous structure, and the second surface 21a of the second member 20 does not have an uneven structure 21a1, and the second charged film 22 is polyimide without a porous structure.

[0036] <Comparative Example 2> In comparative example 2, the height H1 of the uneven structure 11a1 on the first surface 11a of the first member 10 is 0.2 mm, the first charged film 12 is polyurethane without a porous structure, the uneven structure 21a1 on the second surface 21a of the second member 20 is not formed, and the second charged film 22 is polyimide without a porous structure.

[0037] <Comparative Example 3> In comparative example 3, the uneven structure 11a1 is not formed on the first surface 11a of the first member 10, and the first charged film 12 is polyurethane without a porous structure, and the uneven structure 21a1 is not formed on the second surface 21a of the second member 20, and the second charged film 22 is a tetrafluoroethylene-hexafluoropropylene copolymer without a porous structure.

[0038] <Comparative Example 4> In comparative example 4, the height H1 of the uneven structure 11a1 on the first surface 11a of the first member 10 is 0.5 mm, the first charged film 12 is polyurethane without a porous structure, the height H2 of the uneven structure 21a1 on the second surface 21a of the second member 20 is 0.2 mm, and the second charged film 22 is a tetrafluoroethylene-hexafluoropropylene copolymer without a porous structure.

[0039] <Comparative Example 5> In comparative example 5, the height H1 of the uneven structure 11a1 on the first surface 11a of the first member 10 is 0.5 mm, the first charged film 12 is polyurethane without a porous structure, the height H2 of the uneven structure 21a1 on the second surface 21a of the second member 20 is 0.5 mm, and the second charged film 22 is a tetrafluoroethylene-hexafluoropropylene copolymer without a porous structure.

[0040] <Comparative Example 6> In comparative example 6, the first surface 11a of the first member 10 does not have a concave-convex structure 11a1, the first charged film 12 is polyurethane without a porous structure, and the second surface 21a of the second member 20 does not have a concave-convex structure 21a1, and the second charged film 22 is polyimide with a porous structure.

[0041] <Example 1> In Example 1, the height H1 of the uneven structure 11a1 on the first surface 11a of the first member 10 is 0.5 mm, the first charged film 12 is polyurethane without a porous structure, the height H2 of the uneven structure 21a1 on the second surface 21a of the second member 20 is 0.2 mm, and the second charged film 22 is polyimide with a porous structure.

[0042] <Example 2> In Example 2, the height H1 of the uneven structure 11a1 on the first surface 11a of the first member 10 is 0.5 mm, the first charged film 12 is polyurethane without a porous structure, the height H2 of the uneven structure 21a1 on the second surface 21a of the second member 20 is 0.5 mm, and the second charged film 22 is polyimide with a porous structure.

[0043] <Example 3> In Example 3, the height H1 of the uneven structure 11a1 on the first surface 11a of the first member 10 is 0.2 mm, the first charged film 12 is polyamide without a porous structure, the height H2 of the uneven structure 21a1 on the second surface 21a of the second member 20 is 0.2 mm, and the second charged film 22 is polyimide with a porous structure.

[0044] <Example 4> In Example 4, the height H1 of the uneven structure 11a1 on the first surface 11a of the first member 10 is 0.2 mm, the first charged film 12 is polyamide without a porous structure, the height H2 of the uneven structure 21a1 on the second surface 21a of the second member 20 is 0.5 mm, and the second charged film 22 is polyimide with a porous structure.

[0045] <Example 5> In Example 5, the height H1 of the uneven structure 11a1 on the first surface 11a of the first member 10 is 0.5 mm, the first charged film 12 is polyamide without a porous structure, the height H2 of the uneven structure 21a1 on the second surface 21a of the second member 20 is 0.5 mm, and the second charged film 22 is polyimide with a porous structure.

[0046] 4 is a graph showing the results of a test on the generated voltage for the power generators 1 of Comparative Examples 1, 3, and 6. In Comparative Examples 1, 3, and 6, the uneven structure 11a1 is not formed on the first surface 11a of the first electrode portion 11, and the uneven structure 21a1 is not formed on the second surface 21a of the second electrode portion 21. For this reason, Comparative Examples 1, 3, and 6 show that the generated voltage is less than 20 volts.

[0047] FIG. 5 is a graph showing the test results on the generated voltage for Comparative Examples 2, 4, and 5 and Examples 1, 2, 3, and 4. In Comparative Examples 2, 4, and 5 and Examples 1, 2, 3, and 4, an uneven structure is formed on at least one of the first surface 11a and the second surface 21a. Therefore, in Comparative Examples 2, 4, and 5 and Examples 1, 2, 3, and 4, even the low generated voltage is 50 volts or more. In addition, in Examples 1, 2, 3, and 4 in which the second charged film 22 is made of polyimide having a porous structure, the amount of electricity carried increases due to the increase in the surface area of ​​the second charged film 22, so the generated voltage is at least 200 volts or more, and the generated voltage is higher than that in Comparative Examples 2, 4, and 5 in which the second charged film 22 is made of a material without a porous structure.

[0048] 6 is a graph showing the results of a test to measure the relationship between the number of times of power generation in which the first state and the second state are repeatedly switched and the amount of power generation for Comparative Example 5 and Examples 3, 4, and 5. It can be seen that, compared to Comparative Example 5 in which the second charged film 22 does not have a porous structure, Examples 3, 4, and 5 have a smaller rate of decrease in the amount of power generation even when the number of times of power generation increases. It can also be seen that, in Examples 3, 4, and 5, as the sum of the height H1 of the concave-convex structure 11a1 and the height H2 of the concave-convex structure 21a1 increases, the state in which the change in the contact area between the first charged film 12 and the second charged film 22 between the first state and the second state remains large, and the rate of decrease in the relative amount of power generation decreases.

[0049] Fig. 7 is a graph showing the relationship between the sum of the height H1 of the uneven structure 11a1 and the height H2 of the uneven structure 21a1 and the output fluctuation rate, which indicates the maximum rate of decrease in the amount of power generated when the amount of power generated becomes relatively the smallest when switching between the first state and the second state is repeated, for Examples 3, 4, and 5. Fig. 7 shows that the output fluctuation rate decreases as the sum of the height H1 of the uneven structure 11a1 and the height H2 of the uneven structure 21a1 increases.

[0050] 8 shows the generated voltage when the average pore diameter D of the pores 22a of the porous structure is 100 nm, 300 nm, and 2500 nm in Example 2. When the average pore diameter D is 100 nm, the generated voltage is about 170 volts, when the average pore diameter D is 300 nm, the generated voltage is about 370 volts, and when the average pore diameter D is 2500 nm, the generated voltage is about 80 volts. Thus, when the average pore diameter D of the pores 22a is 300 nm, the generated voltage is higher than when the average pore diameter D is 100 nm or 2500 nm.

[0051] Thus, the power generator 1 of this embodiment comprises a first member 10 having a first surface 11a covered with a first charged film 12, and a second member 20 having a second surface 21a covered with a second charged film 22, and generates power by changes in the contact state between the first surface 11a and the second surface 21a, whereby uneven structures 11a1, 21a1 are formed over the entire surface of the first surface 11a and the second surface 21a, and the second charged film 22 is made of a material having a porous structure.

[0052] As a result, by using a porous material as second charged film 22, it is possible to increase the amount of electricity carried by the second charged film, thereby preventing the film from becoming large and increasing the amount of power generated.

[0053] Furthermore, when the uneven structure 11a1, 21a1 is formed only on one of the first surface 11a and the second surface 21a, it is preferable that the distance between the top and bottom of the uneven structure 11a1, 21a1 is 0.3 mm or more, and when the uneven structure 11a1, 21a1 is formed on both the first surface 11a and the second surface 21a, it is preferable that the sum of the distance H1 between the top and bottom of the uneven structure 11a1 formed on the first surface 11a and the distance H2 between the top and bottom of the uneven structure 21a1 formed on the second surface 21a is 0.3 mm or more.

[0054] As a result, the rate of decrease in the relative amount of power generated is lowered when power generation is repeated, and the rate of output fluctuation is reduced, thereby improving durability and improving the stability of the output.

[0055] Moreover, the first charging film 12 is made of polyamide, and the second charging film 22 is made of porous polyimide.

[0056] This makes it possible to improve the generated voltage and further increase the amount of generated power.

[0057] The average pore size D of the second charging film 22 is not less than 200 nm and not more than 400 nm.

[0058] This makes it possible to increase the generated voltage compared to other average hole diameters D, and therefore to increase the amount of generated electricity.

[0059] In the above embodiment, the first charged film 12 is formed from a member that does not have a porous structure, and the second charged film 22 is formed from a member that has a porous structure, but this is not limited to this. For example, the first charged film 12 may be formed from a member that has a porous structure, and the second charged film 22 may be formed from a member that does not have a porous structure, or both the first charged film and the second charged film may be formed from a member that has a porous structure, as long as at least one of the first charged film and the second charged film is formed from a member that has a porous structure.

[0060] In addition, in the above embodiment, polyimide is shown as a material having a porous structure, but this is not limited thereto, and materials other than polyimide may be used as long as they are capable of forming a porous structure.

[0061] In the above embodiment, the power generator 1 generates power by applying a force from the outside in a direction that presses the first charged film 12 and the second charged film 22 against the first member 10 and the second member 20 against each other, but the present invention is not limited to this. The present invention is also applicable to a power generator that generates power by applying a force from the outside in a direction that moves the first member and the second member along the first surface and the second surface of the first charged film and the second charged film in contact with each other. [Explanation of symbols]

[0062] 1 Power generation unit 10 First member 11 First electrode part 11a 1st page 11a1 Uneven structure 12 First charging film 20 Second member 21 Second electrode part 21a 2nd side 21a1 Uneven structure 22 Second Charged Film

Claims

1. A power generating unit comprising: a first member having a first surface covered with a first charged film; and a second member having a second surface covered with a second charged film, the power generating unit generating power by a change in a contact state between the first surface and the second surface, At least one of the first surface and the second surface has an uneven structure formed over the entire surface, At least one of the first charging film and the second charging film is made of a member having a porous structure, the first electrostatic film is made of polyamide; the second charging film is made of polyimide having a porous structure, The second charged film does not include an amide bond in which a part of the imide bond of the polyimide is ring-opened. Power generating body.

2. When the uneven structure is formed only on one of the first surface and the second surface, the height from the bottom to the top of the uneven structure is 0.3 mm or more; When the uneven structure is formed on both the first surface and the second surface, the sum of the height from the bottom to the top of the uneven structure formed on the first surface and the height from the bottom to the top of the uneven structure formed on the second surface is 0.3 mm or more. The power generating unit according to claim 1 .

3. The member having a porous structure has an average pore size of 200 nm or more and 400 nm or less. The power generating unit according to claim 1 or 2.

Citation Information

Patent Citations

  • Power generation body, power generator and pressure sensor

    JP2018191454A

  • Power generator

    JP2020092582A